Paris on the Mekong: using the aid effectiveness agenda to support human resources for health in the Lao People's Democratic Republic - Hill Peter S; Dodd Rebecca; Shuey Dean; Fernandes Antunes Adélio (BMC, 2009)
Abstract Background This study examines the potential of aid effectiveness to positively influence human resources for health in developing countries, based on research carried out in the Lao People's Democratic Republic (Lao PDR). Efforts to make aid more effective - as articulated in the 2005 Paris Declaration and recently reiterated in the 2008 Accra Agenda for Action - are becoming an increasingly prominent part of the development agenda. A common criticism, though, is that these discussions have limited impact at sector level. Human resources for health are characterized by a rich and complex network of interactions and influences - both across government and the donor community. This complexity provides a good prism through which to assess the potential of the aid effectiveness agenda to support health development and, conversely, possibilities to extend the impact of aid-effectiveness approaches to sector level. Methods The research adopted a case study approach using mixed research methods. It draws on a quantitative analysis of human resources for health in the Lao People's Democratic Republic, supplementing this with a documentary and policy analysis. Qualitative methods, including key informant interviews and observation, were also used. Results The research revealed a number pathways through which aid effectiveness is promoting an integrated, holistic response to a range of human resources for health challenges, and has identified further opportunities for stronger linkages. The pathways include: (1) efforts to improve governance and accountability, which are often central to the aid effectiveness agenda, and can be used as an entry point for reforming workforce planning and regulation; (2) financial management reforms, typically linked to provision of budget support, that open the way for greater transparency and better management of health monies and, ultimately, higher salaries and revenues for health facilities; (3) commitments to harmonization that can be used to improve coherence of donor support in areas such as salary supplementation, training and health information management. Conclusion If these opportunities are to be fully exploited, a number of constraints will need to be overcome: limited awareness of the aid effectiveness agenda beyond a core group in government; a perception that this is a donor-led agenda; and different views among partners as to the optimal pace of aid management reforms. In conclusion, we recommend strategic engagement of health stakeholders in the aid effectiveness agenda as one means of strengthening the health workforce.